Issues of Improving the Principles of Civil Proceedings (Lembaga Contrarius Indonesia, 2026)
This article provides a scientific and theoretical analysis of the principles of civil proceedings and issues of their improvement. In particular, the opinions of legal scholars regarding the concept of the principle of legality and its significance in civil proceedings were analyzed and a scientific definition of this principle was given. Similarly, a scientific and theoretical analysis of the principle of free law initiating and activating civil proceedings and the principle of adversarial nature of the parties and their role in judicial practice, the opinions of legal scholars on this issue, as well as a comparative study of the civil procedural legislation of foreign countries and scientific and theoretical conclusions and proposals were given. In the article, the author paid special attention to the issue of the inadmissibility of abuse of procedural rights and highlighted its specifics. Having analyzed how abuse of procedural rights manifests itself and having studied scientific and theoretical concepts on this matter, a scientific definition of this concept was developed. Also, on issues of principles of civil proceedings, a comparative study was conducted of national civil procedural legislation with the civil procedural legislation of foreign countries, in particular the Constitutions of Japan, Greece, Bulgaria, Germany and the civil procedural legislation of the Russian Federation, Estonia, Armenia, Ukraine, Belarus, Kazakhstan, Kyrgyzstan. Scientific and theoretical conclusions, proposals and recommendations aimed at improving the principles of civil proceedings have been put forward.